Clinical, ultrasound and chromosome findings of testicles in a French bulldog (Canis lupus familiaris) with azoospermia - Agudelo-Yepes, Salome (Array, 2020)
This case report describes azoospermia in a French bulldog. The dog, with historical evidence of unsuccessful insemination after both artificial insemination and natural breeding, presented with physiological parameters (testosterone levels and karyotype) within normal ranges. Scrotal palpation and ultrasound of both testicles indicated aplasia of the epididymis and vas deferens. Two seminal samples were examined and no sperm cells were found. In conclusion, before starting an assisted reproduction procedure, it is necessary to perform sperm analysis to determine the reproductive capacity of the dog intended as a stud dog.